Photodynamic and Antibiotic Therapy Impair the Pathogenesis of Enterococcus faecium in a Whole Animal Insect Model - Chibebe Junior, José [UNESP]; Fuchs, Beth B.; Sabino, Caetano P.; Junqueira, Juliana Campos [UNESP]; Jorge, Antonio O. C. [UNESP]; Ribeiro, Martha S.; Gilmore, Michael S.; Rice, Louis B.; Tegos, George P.; Hamblin, Michael R.; Mylonakis, Eleftherios (Public Library of Science (PLoS), 2013)
Enterococcus faecium has emerged as one of the most important pathogens in healthcare-associated infections worldwide due to its intrinsic and acquired resistance to many antibiotics, including vancomycin. Antimicrobial photodynamic therapy (aPDT) is an alternative therapeutic platform that is currently under investigation for the control and treatment of infections. PDT is based on the use of photoactive dye molecules, widely known as photosensitizer (PS). PS, upon irradiation with visible light, produces reactive oxygen species that can destroy lipids and proteins causing cell death. We employed Galleria mellonella (the greater wax moth) caterpillar fatally infected with E. faecium to develop an invertebrate host model system that can be used to study the antimicrobial PDT (alone or combined with antibiotics). In the establishment of infection by E. faecium in G. mellonella, we found that the G. mellonella death rate was dependent on the number of bacterial cells injected into the insect hemocoel and all E. faecium strains tested were capable of infecting and killing G. mellonella. Antibiotic treatment with ampicillin, gentamicin or the combination of ampicillin and gentamicin prolonged caterpillar survival infected by E. faecium (P = 0.0003, P = 0.0001 and P = 0.0001, respectively). In the study of antimicrobial PDT, we verified that methylene blue (MB) injected into the insect followed by whole body illumination prolonged the caterpillar survival (P = 0.0192). Interestingly, combination therapy of larvae infected with vancomycin-resistant E. faecium, with antimicrobial PDT followed by vancomycin, significantly prolonged the survival of the caterpillars when compared to either antimicrobial PDT (P = 0.0095) or vancomycin treatment alone (P = 0.0025), suggesting that the aPDT made the vancomycin resistant E. faecium strain more susceptible to vancomycin action. In summary, G. mellonella provides an invertebrate model host to study the antimicrobial PDT and to explore combinatorial aPDT-based treatments.
Keywords: ampicillin; gentamicin; methylene blue; phenothiazinium; photosensitizing agent; streptomycin; unclassified drug; vancomycin; antibiotic resistance; antibiotic sensitivity; antibiotic therapy; bacterial strain; caterpillar; combination chemotherapy; controlled study; drug efficacy; drug response; enterococcal infection; Enterococcus faecium; Galleria mellonella; in vivo study; infection control; nonhuman; pathogenesis; photodynamic therapy; survival rate; vancomycin resistant Enterococcus; Animals; Anti-Bacterial Agents; Disease Models, Animal; Gram-Positive Bacterial Infections; Methylene Blue; Moths; Photochemotherapy; Photosensitizing Agents